MONITORING GEOSYSTEMS OF SPECIALLY PROTECTED NATURAL TERRITORIES IN THE CONDITIONS OF ANTHROPOGENOUS LOAD - A. A. Lazareva; A. A. Slauta; T. E. Afonina (Наука. Инновации. Технологии)
Introduction: The state of the environment is an urgent problem of the present time. Specially protected natural areas are the basis of territorial protection of the natural environment. The category of protected areas is determined by the law "on specially protected natural areas", each of which has its own characteristics of environmental activities. Depending on the status of protected areas, their mode of use is determined, but despite this they are subjected to various anthropogenic impacts. In this regard, there is a need for systematic monitoring of the dynamics of the state of geosystems and objective assessment of negative processes. In this article the complex monitoring of especially protected natural territories on the example of Tunka national Park and the Central ecological zone of the South-East coast of oz is considered. Baikal. Materials and methods of research: Tunkinsky National Park is located in the South-Western part of the Republic of Buryatia, this Park was created geographically within the administrative boundaries of Tunka district. Like the Tunka national Park, the coast of lake Baikal suffers irreparable environmental damage: the forest is cut down, the mouths of rivers are polluted, the coast is littered with garbage, the vegetation is trampled down and as a result of these impacts leads to the disappearance of rare plant species. Comprehensive monitoring includes the collection of operational information on the state of geosystems, quantitative and qualitative accounting for the processes of anthropogenic impact by laying test sites and detailed observation of them. Forest fire monitoring is the collection of information on forest fires and the area of damaged plantations for further prediction and assessment of the actual burning of forest geosystems. The process of natural regeneration of forests is studied on the felling and felling. Assessment of recreational load is carried out on the territories popular for tourists. Forest pathology and sanitary conditions of forest geosystems are assessed in the zone of anthropogenic impact and other factors. The results of the study and their discussion: Analysis of monitoring of forest fires showed a decrease in their number over the past 15 years, but the area of dead plantations reaches maximum values. According to the survey of plantations covered by fire, recovery is not expected in a large area of test areas. Weakened trees are susceptible to future insect infestation. The massive summer influx of unorganized vacationers leads to the excess of environmentally acceptable standards, which leads to a critical ecological and sanitary condition of the Park's geosystems and the South-East coast of the lake. Baikal. The renewal of forests in the Park is noted on abandoned agricultural land. The distribution of self-seeding is uneven, but viable. Findings: During the period of regular observations revealed that the main cause of death and weakening of the geosystems of the national Park "Tunkinsky" -forest fires, and on the South-East coast of the lake. Baikal is an uncontrolled tourist low. Adverse weather conditions have also had irreversible effects on the health of forest geosystems. This applies to phenomena that are catastrophic, such as mudflows, floods, windfalls. In the absence of thinning on the surveyed sample areas is predicted deterioration of forest plantations. In a depressed state, rare species of plants are exposed to recreational effects in the territories under consideration.